Pengaruh Peraturan Bank Indonesia Tentang Kredit UMKM Terhadap Total Kredit, Rasio Kredit Umkm, Risiko, Efisiensi dan Profitabilitas Bank Pembangunan Daerah - Bagus Santosa; Yanuar Yanuar (Universitas Tarumanagara, 2020)
This research aims to analyze the effect of Bank of Indonesia Regulation on Micro, Small, and Medium Enterprises (MSME) loans towards the Loan Disbursed, MSME Loan Ratio, Risk, Efficiency, and Profitability of Regional Development Banks. This research analyzes the financial data from 10 BPDs over 10 years period to understand the Loan Disbursed, MSME Loan Ratio, Risk, Efficiency, and Profitability of the BPDs before and after the implementation of Regulation Number 14/22/PBI/2012. The financial data were analyzed using the Paired-Sample t-test. Findings show that the overall loan disbursed by BPDs in the period of 2013-2017 or after the Regulation on MSME loans was implemented, is higher than that in the period of 2008-2012 or before the regulation was implemented. However, while the regulation aims to increase the MSME loan disbursed by the banks, the MSME Loan Ratio in the period of 2013-2017 was lower than that in the period of 2008-2012. The Risk, measured by Non-Performing Loan, in the period of 2013-2017 was also increased. The regulation also affects the profitability of the BPDs negatively. The Efficiency, measured by Operating Expenses Operating Income, was not significantly affected by the regulation. The results may inform the regulators to assist the BPDs in responding to the regulation so it could affect BPDs in a more positive way. This may also inform the banks on their financial conditions so they can plan for strategic approaches and develop appropriate schemes on disbursing MSME loans.